2023
DOI: 10.1155/2023/3660968
|View full text |Cite
|
Sign up to set email alerts
|

Stability and Survivability of Alginate Gum-Coated Lactobacillus rhamnosus GG in Simulated Gastrointestinal Conditions and Probiotic Juice Development

Abstract: Survivability of probiotics is severely affected by harsh gastrointestinal conditions. In the present study, microbeads of Lactobacillus rhamnosus GG were formulated using alginate (1.5% w/v) and combination of alginate (1.5% w/v) with xanthan gum (0.5% w/v) through an emulsion technique to improve bacterial viability in low pH orange juice and in gastrointestinal conditions. The microbeads were tested for encapsulation efficiency, survivability in bile salt, SGF (simulated gastric juice), SIF (simulated intes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 65 publications
0
10
0
1
Order By: Relevance
“…The encapsulation of probiotics was carried out by adopting the method of Azam et al (2020) with slight modifications. Sodium alginate (SA, 1.5% w/v) and xanthan gum (XG, 0.5% w/v) were used for coating of the L. rhamnosus GG through homogenisation emulsification methods as documented in our preliminary trials conducted in our earlier study Ali et al (2023). Sodium alginate and xanthan gum powders were mixed with distilled water (100.0 mL) and stirred up to 80 °C to form a clear mixture.…”
Section: Encapsulation Through Homogenisation Emulsification Methodsmentioning
confidence: 99%
“…The encapsulation of probiotics was carried out by adopting the method of Azam et al (2020) with slight modifications. Sodium alginate (SA, 1.5% w/v) and xanthan gum (XG, 0.5% w/v) were used for coating of the L. rhamnosus GG through homogenisation emulsification methods as documented in our preliminary trials conducted in our earlier study Ali et al (2023). Sodium alginate and xanthan gum powders were mixed with distilled water (100.0 mL) and stirred up to 80 °C to form a clear mixture.…”
Section: Encapsulation Through Homogenisation Emulsification Methodsmentioning
confidence: 99%
“…Citrus slices were utilized for palate cleansing during the sensory evaluation. The sensory acceptability scale was 1: disliked extremely to 9: liked extremely …”
Section: Methodsmentioning
confidence: 99%
“…Previous studies have demonstrated the combined effect of alginate with other food polymers as viable encapsulation materials vs alginate alone due to its ability to withstand highly acidic conditions in human stomach . Previous studies have identified the combined use of sodium alginate and carrageenan gums for probiotic encapsulation, leveraging their broad bioadaptability, versatility, heat resistance, and effectiveness in low pH conditions . These coating materials, known for their nontoxicity, affordability, and ease of handling, are particularly suitable for encapsulation.…”
Section: Introductionmentioning
confidence: 99%
“…Probiotics are live microorganisms that provide health benefits to the host when ingested in sufficient quantities (Shi et al ., 2016). They are resistant to digestive juices and can adhere to and settle on mucous membranes and epithelial linings (Ali et al ., 2023). Probiotics are more unstable in non‐dairy products than in dairy products (Nazzaro et al ., 2009), and their viability may decrease as they pass through the digestive tract during ingestion.…”
Section: Introductionmentioning
confidence: 99%